The cost of corrosion in China - Baorong Hou (Nature Portfolio, 2017)
Economics: What corrosion cost China in 2014 It is estimated that the effects of corrosion in China cost approximately $310 billion USD in 2014. Corrosion is a costly issue, justifying substantial expenditure into techniques to protect and mitigate susceptible metals from its effects, and research investment. China has seen rapid growth in its economy in recent times, driven in part by investment in industry. In order to understand the monetary impact of corrosion in China, The Chinese Academy of Engineering instigated a nationwide study led by the Institute of Oceanology, Chinese Academy of Sciences. It estimates that approximately $310 billion USD was lost to the consequences of corrosion and money spent addressing it in 2014, accounting for 3.34% of GDP. Transportation and electronics industries generated the highest costs. Several recommendations are made, including the need for a government-coordinated national strategy.